MATKI W POPKULTURZE – ZWYKŁE CZY NIEZWYKŁE? O EKSPERTYZACJI MACIERZYŃSTWA W DYSKURSIE MEDIALNYM - Szulich-Kałuża, Justyna (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The theme of the article are expertisation of the motherhood in the media. It is a study about the issue of the growing importance of experts in the postmodern societies, which replaces the traditional opinion leaders, intellectuals and scientists. The author refers to the dimensions of expertisation of the motherhood including the asymmetry in the relationship of a mother and a child, the asymmetry in relations between a mother and an expert, the asymmetry in the relationship between personal knowledge and expertise knowledge, instructions of experts, the lack of qualifications and skills of mothers in their role of a mother. The dimensions are discussed on the basis of the discourse of experts about motherhood in TV-programm ”I Ty możesz mieć superdziecko”.